UNION MILITANTS IN JUJUY, ARGENTINA. A STUDY OF POLITICAL COMMITMENT FROM A CAREER PERSPECTIVE - Berardi Spairani, Adrián Pablo (2022)
This article analyzes the union militancy in the province of Jujuy, Argentina between the years 2015 and 2017. The objective is to give an account of the elements that condition and determine the political commitment of this type of militancy. We worked with a microstructural jib and used a qualitative methodology based on the life story. It was possible to identify that militant career share common sequences, but political practices and views of their own militancy differ in that they are conditioned by their spaces of participation.